7-octave high-brightness CEP-stable light source - Elu, U.; Maidment, L.; Vamos, L.; Tani, F.; Novoa, D.; Frosz, M. H.; Badikov, V.; Badikov, D.; Petrov, V.; Russell, P. St J.; Biegert, J. (Optics InfoBase Conference Papers, 2022)
We present a carrier-envelope-phase stable light source, seeded by a mid-IR frequency comb, with simultaneous spectral coverage across 7 optical octaves, from the UV (340 nm) into the THz (40,000 nm).
CRIS-Team Scopus Importer:2022-09-09